Sebaran Suhu Permukaan Laut Teluk Lampung berdasarkan Citra Landsat-8 dan Kaitannya terhadap Indian Ocean Dipole (IOD) Periode Tahun 2013 – 2021: Sea Surface Temperature Distribution in Lampung Bay Based on Landsat-8 Images and its Relation to the Indian Ocean Dipole (IOD) on the Period Year 2013-2021 (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2023)
Sea surface temperature is an important oceanographic attribute in ocean waters, that changes of sea water temperature can change aquatic ecosystems. Lampung Bay waters originating from the Indian Ocean and the Java Sea which pass through the Sunda Strait will be influenced by the Indian Ocean Dipole (IOD). This study aims to analyze spatial and temporal inter-annual Sea Surface Temperature (SST) distribution patterns in the last 9 years (2013-2021) and analyze the Indian Ocean Dipole (IOD) phenomenon that caused an anomaly of SST in Lampung Bay. The method used in this study is a regression validation method, descriptive method and correlative statistics. The results showed that the SST value of Landsat-8 image extraction can represent in situ SST conditions because R2=0.6872. The IOD phenomenon influences the Lampung Bay water’s SST distribution pattern. Positive IOD phase years (2015, 2018 and 2019) or negative IOD phases (2013 and 2016) shown SST of Lampung Bay waters has a different distribution pattern and anomalous values. But correlation between IOD and SST in Lampung Bay had two different result which in open water (TL3, TL4, and TL5) is mid-correlate (r>0.7) and weak correlation (r